Fulfilling a social mission: Examining practice locations of residency graduates over two decades - Dubé, Tim; Touchette, Matthieu; Bergeron, Linda; Fourati, Mariem; Barber, Cassandra; St-Onge, Christina (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Background: Medical schools play a critical role in shaping the physician workforce. Tracking the practice locations of medical graduates is essential for addressing healthcare disparities and workforce shortages in underserved regions. This study examines the geographic distribution of residency graduates from a Canadian francophone university, aligning their practice locations with the university’s social accountability mandate.Methods: A cross-sectional descriptive study was conducted using data from the Canadian Post-M.D. Education Registry (CAPER) for 2,410 residency graduates (2000-2020) from 35 residency training programs. We analyzed practice locations at two-, five-, and 10-years post-graduation across medical specialties, sex, and geographic region, with a focus on Quebec’s administrative health regions.Results: There were 2,410 graduates from 35 residency training programs. Family medicine accounted for 57.8% of all graduates and 42.2% were from all other specialties. Most graduates (77.7%) practiced in the province of Quebec, with concentrations in the regions of the Eastern Townships (19.4%), Montérégie (14.6%), and Saguenay-Lac-St-Jean (7.6%).Conclusion: This study demonstrates the important regional impact of the university’s role in training family physicians and addressing healthcare needs in Quebec. The findings suggest the importance of tracking to inform evidence-based workforce planning and policy development. Medical schools can leverage such data to align training programs with societal health needs and enhance their contributions to regional healthcare systems.